Customer satisfaction at Bank Rakyat customer service: case study on Bank Rakyat head quarters / Siti Shahayu Mohd Rafdzi - Mohd Rafdzi, Siti Shahayu (2015)
This research is to study several factor which is protections on customer personel information, bank service quality and bank responsibility as the variable that may influence the customer satisfaction at Bank Rakyat customer services. This research helps to determine customer satisfaction of Bank Rakyat customer at Kuala Lumpur area. The variable is help to determine the most influencing factor towards the customer satisfaction. The data originally consist of 5 dimension data analysis which include descriptive analysis, frequencies analysis, Pearson correlations coefficient analysis, reliability analysis and multiple regression analysis. This model helps to evaluate the customer satisfaction at Bank Rakyat customer services.